2018
DOI: 10.1016/j.rvsc.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral effect of lithium chloride on porcine epidemic diarrhea virus in vitro

Abstract: Porcine epidemic diarrhea virus (PEDV), a member of the Coronaviridae family, causes acute diarrhea, vomiting, dehydration, and high mortality rates in neonatal piglets. Severe outbreaks of PEDV variants have re-emerged in Asia and North America since 2010, causing tremendous economic losses to the swine industry. The lack of effective therapeutic treatment promotes the research for new antivirals. Lithium chloride (LiCl) has been reported as a potential antiviral drug for certain viruses. In this study, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 34 publications
1
36
2
1
Order By: Relevance
“…This raised the possibility that lithium could possess meaningful in vivo activity against RNA viruses. More recent research suggests that lithium has at least in vitro activity against several coronaviruses, including both gastrointestinal and respiratory pathogens (Harrison, Tarpey, Rothwell, Kaiser, & Hiscox, 2007; Li et al, 2018; Ren et al, 2011). A recent review (Nowak & Walkowiak, 2020) examined these studies critically and concluded that lithium, either alone or in combination with chloroquine, merited further investigation as a treatment for SARS‐CoV‐2.…”
Section: Action Mechanism Referencesmentioning
confidence: 99%
“…This raised the possibility that lithium could possess meaningful in vivo activity against RNA viruses. More recent research suggests that lithium has at least in vitro activity against several coronaviruses, including both gastrointestinal and respiratory pathogens (Harrison, Tarpey, Rothwell, Kaiser, & Hiscox, 2007; Li et al, 2018; Ren et al, 2011). A recent review (Nowak & Walkowiak, 2020) examined these studies critically and concluded that lithium, either alone or in combination with chloroquine, merited further investigation as a treatment for SARS‐CoV‐2.…”
Section: Action Mechanism Referencesmentioning
confidence: 99%
“…In Vero cells, lithium chloride (investigated at 1-15 mM) was shown to be dose-dependently effective in suppressing infection with the porcine epidemic diarrhea virus (PEDV), a member of the Coronaviridae family 1 . Not only PEDV entry and replication were inhibited in the presence of LiCl, but apoptosis as well.…”
Section: Resultsmentioning
confidence: 99%
“…In Vero cells, lithium chloride was shown to be effective in suppressing infection with the porcine epidemic diarrhea virus (PEDV), a member of the Coronaviridae family 1 . Not only PEDV entry and replication were inhibited in the presence of LiCl, but apoptosis as well.…”
Section: Resultsmentioning
confidence: 99%